2014
DOI: 10.3390/insects5040832
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Liquid and Bait Insecticides against the Dark Rover Ant (Brachymyrmex patagonicus)

Abstract: Dark rover ants (Brachymyrmex patagonicus, Mayr) are an exotic ant species native to South America that has recently spread through the southern US. We evaluated the residual activity of three liquid insecticides (indoxacarb, fipronil and lambda-cyhalothrin) as potential barrier treatments against these ants. The factors we considered include the use of a porous or non-porous surface, a short or long exposure time and the changes in insecticide activity after treatment during a 90 day period. We also tested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…(2003) found that spraying insecticides in citrus, guava and mango tree plantations eliminated the dominant arboreal ant. Miguelena and Baker (2014) stated that it is vital to consider the residual activity of insecticides observed in the indoor experiment, which may not be the same if applied outdoors. Most likely, the insecticides lose their efficacy faster.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2003) found that spraying insecticides in citrus, guava and mango tree plantations eliminated the dominant arboreal ant. Miguelena and Baker (2014) stated that it is vital to consider the residual activity of insecticides observed in the indoor experiment, which may not be the same if applied outdoors. Most likely, the insecticides lose their efficacy faster.…”
Section: Resultsmentioning
confidence: 99%
“…Most likely, the insecticides lose their efficacy faster. According to Miguelena and Baker (2014) , ant mortality using insecticides treatment is important. It opens the possibility for the transfer of the insecticide from exposed to unexposed ants via contacts through social interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Laboratory evidence suggests that several common active ingredients have reduced efficacy against dark rover ants 44,55 . However, baits containing imidacloprid are highly effective against this species, 55 thus the colonies that persisted around the treatment structures may not have acquired the bait. Many of the rover ant colonies were found in the same general area after 28 days (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…19 Indoxacarb and lambda-cyhalothrin were found effective against rover antsas potential barrier treatment, 20 while quinalphos and imidacloprid are used against planthoppers. 21 Moreover, farmers also apply different insecticides at indiscriminate rates and frequencies to overcome pest problems, leading to pest resurgence and destruction of natural enemies. [22][23] Ants are caught and dragged away from the predators from aphids in the field and disturb the biological control.…”
Section: Introductionmentioning
confidence: 99%